2020
DOI: 10.2106/jbjs.20.00124
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Scaphoid Fractures with High-Resolution Peripheral Quantitative CT Compared with Conventional CT

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The CT also has a high specificity but a lower sensitivity; however, it is often preferred to the MRI as it is cheaper and more readily available (1,4,5). High-resolution peripheral quantitative computed tomography (HR-pQCT) represents an innovative option in detecting scaphoid fractures (6)(7)(8). Since the first results have only recently been published, its use is not yet widely established in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CT also has a high specificity but a lower sensitivity; however, it is often preferred to the MRI as it is cheaper and more readily available (1,4,5). High-resolution peripheral quantitative computed tomography (HR-pQCT) represents an innovative option in detecting scaphoid fractures (6)(7)(8). Since the first results have only recently been published, its use is not yet widely established in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high resolution, small fissures in the scaphoid bone can be detected more sensitively than with the conventional CT (6,22). Furthermore, the analysis of the bone mineral density and micro-architecture could help to provide insights into fracture mechanisms, the non-union etiology (7), and its biology (23) and quantify the healing process of scaphoid fractures (16).…”
Section: Introductionmentioning
confidence: 99%
“…The patient's forearm was placed in an anatomically shaped motion-restraining holder to obtain a standardized position. Detailed information regarding the scanning procedures, image reconstruction, and fracture assessment was described previously [7,15].…”
Section: Hr-pqctmentioning
confidence: 99%
“…High-resolution peripheral quantitative CT (HR-pQCT), a novel imaging technique that allows an assessment of the microstructure of cortical and trabecular bone at the distal radius and tibia, has recently been introduced [11, 13, 17-19, 31, 39]. Because there is no consensus regarding the reference imaging technique for diagnosing scaphoid fractures, we have studied HR-pQCT as a diagnostic tool and have shown that it is feasible [7, 16] and superior [15] to CT for detecting fractures in patients with a clinically suspected scaphoid fracture. Therefore, we compared the results of conventional radiographs and clinical reassessment with HR-pQCT in this study.…”
Section: Introductionmentioning
confidence: 99%
“…To do this, we need a trustworthy gold standard against which we can test those alternatives. Current studies [1,2,4] have shown the superiority of highresolution peripheral quantitative CT over conventional CT; therefore, this method might serve us well as a gold standard when evaluating other diagnostic methods.…”
mentioning
confidence: 99%